Alliance Adjustment in the Post‐Cold War Era: Convergence of Strategic Perceptions and Revitalization of the ROK–US Alliance. (April 2015) - Kim, Jaechun
<x xml:space="preserve">Abstract</x> The ROK–US alliance has survived the tumultuous periods following the demise of the Cold War international order and morphed into what both countries identify as a global, value‐based partnership. Skeptical assessments of the alliance's future seemed to have overlooked a number of factors. First, domestic politics can make a big difference; political leadership can play a crucial role in salvaging or damaging alliance partnership. Second, the importance of shared values and identities looms larger in modern alliances. States tend to ally with others to cope with uncertainties, not necessarily to counter manifest threats. Alliances can survive the disappearance of the common threats that had given rise to the alliances and they can be sustained in order to further various interests. All these factors and dynamics help account for why the ROK–US alliance has survived the post‐Cold War adversity. Nevertheless, these factors alone come short of explaining why the alliance has elevated to a core of US security strategy in the region; they do not explain why the alliance once again has come to occupy the very heart of the ROK's security strategy. It was the divergent strategic perceptions that mostly frayed the alliance in the first place, and it was the convergence of strategic perceptions that brought the alliance back together.